1997
DOI: 10.1063/1.364276
|View full text |Cite
|
Sign up to set email alerts
|

Effective dielectric constant of random composite materials

Abstract: http://jap.aip.org/The randomness in the structure of two-component dense composite materials influences the scalar effective dielectric constant, in the quasistatic limit. A numerical analysis of this property is developed in this paper. The computer-simulation models used are based on both the finite element method and the boundary integral equation method for two- and three-dimensional structures, respectively. Owing to possible anisotropy the orientation of spatially fixed inhomogeneities of permittivity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
122
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(126 citation statements)
references
References 20 publications
4
122
0
Order By: Relevance
“…[11][12][13][14][15] Needless to say, it is not a simple task for calculating the values of effective permittivity with anisotropic inclusions, [16][17][18][19][20][21][22][23][24] and the effective permittivity varies from different orientations of inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Needless to say, it is not a simple task for calculating the values of effective permittivity with anisotropic inclusions, [16][17][18][19][20][21][22][23][24] and the effective permittivity varies from different orientations of inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations and analytical modeling performed with complex permittivities have investigated only properties at constant frequencies [24,[29][30][31][32][33][34], while very few articles concentrated on the frequency dispersion of binary mixtures [25,[35][36][37][38]. The beauty of investigating the frequency dependent properties of binary mixtures has been many folded; (i) information on system structural properties and how particle shape and dispersion influence the overall composite properties can be studied; (ii) fundamentals of dielectric relaxation and interacting systems can be investigated; (iii) the nature of real systems such as polymers, ionic liquids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current studies based on numerical analysis of 2-D or 3-D structures with two constituents show that the effective properties of the mixture strongly depend on the volume fraction, its geometrical profile and spatial orientation in periodic or random arrangements [9,10]. It has been shown that the macroscopic properties of dielectric-only mixtures can be represented by a homogenous dielectric with an effective permittivity that is determined using an empirical mixing model [11].…”
Section: Introductionmentioning
confidence: 99%